PASAR MODERN DAN PASAR TRADISIONAL DALAM GAYA HIDUP MASYARAKAT DI KABUPATEN TABANAN, PROVINSI BALI - Candrawati, A.A Ketut Sri Candrawati (Universitas 17 Agustus 1945 Surabaya, 2015)
The Lifestyle have a major impact on the purchase and consumption of consumerbehaviour of consumers. From time to time an individual’s lifestyle and particular groupof people will move dynamically. However, lifestyle is rapidly changing, so that at acertain time is relatively permanent lifestyle. The existence of Traditional markets inurban areas from time to time further increasingly threatened by rampant construction ofModern Markets. As we know the impact of the existence of Modern Market to retailbusiness managed by cooperative, Traditional Market small and medium enterprise anddraw up a concept on the empowerment of retail business applied by cooperative,Traditional Market small and medium enterprise. The main problem of this study is (1)the position of Traditional Market and Modern Market seen from institutional aspectand the existing regulation, (2) the impact of the existence of Modern Market to retailbusiness managed by cooperative, Traditional market small and medium enterprise seenin aspect of business volume, selling price, worker number and factors affectingconsumer behaviour in determining to shopping and (3) the concept to empower retailbusiness applied by cooperative, Traditional Market small and medium enterprisesimpact to business volume of Traditional Market. Between before and after theexistence of Modern is quite different, in which the business volume of TraditionalMarket was higher before the existence of Modern Market, while variable of sellingprice and worker number is just a slight difference. Based on the analysis, zoningTraditional Markets and Modern markets is the authority of Local GovernmentDevelopments as stipulated in Presidential Regulation Number 112 year 2007concerning settlement and Development of Traditional, Modern Shopping Centres andwho is the embodiment of law No. 5 year 1999 concerning prohibition of Monopolisticpractices and Unfair Business Competition Healthy.Keyword : Life Style , Traditional Market, Modern Market..